PENGUSAHA TAHU DESA SUMBEREJO WETAN KECAMATAN NGUNUT KABUPATEN TULUNGAGUNG - Andriansyah, Agussalim; Sudiarto, Edi (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
Tofu to have more processed variations compared to tempeh, so many people are more interested in setting up tofu factories. Small-tofu industry is a hereditary activity in several regions, especially in Sumberejo Kulon Village, Ngunut Sub-district, which is one of the small-tofu industry centers in Tulungagung Regency. The small tofu industry is one of the sources of income for the people of Sumberejo Kulon Village. Tofu produced by partners is a type of white tofu or commonly called tofu vegetable. The establishment of the business know aims to fulfill the daily needs of everyday partners and in the future to create wider employment opportunities for the people of Sumberejo Kulon Village in particular and the Tulungagung community in general. The problem faced by related partners in the production process is soybean milling equipment which is currently still using soybean milling services in neighboring partners so that they have to pay for milling services, soy cooking equipment that is less feasible for cooking, less clean production sites, and very knowledgeable limited bookkeeping and management of business management.